Nanoparticles for Magnetic Heating: When Two (or More) Is Better Than One - Jesus G. Ovejero (MDPI AG, 2021)
The increasing use of magnetic nanoparticles as heating agents in biomedicine is driven by their proven utility in hyperthermia therapeutic treatments and heat-triggered drug delivery methods. The growing demand of efficient and versatile nanoheaters has prompted the creation of novel types of magnetic nanoparticle systems exploiting the magnetic interaction (exchange or dipolar in nature) between two or more constituent magnetic elements (magnetic phases, primary nanoparticles) to enhance and tune the heating power. This process occurred in parallel with the progress in the methods for the chemical synthesis of nanostructures and in the comprehension of magnetic phenomena at the nanoscale. Therefore, complex magnetic architectures have been realized that we classify as: (a) core/shell nanoparticles; (b) multicore nanoparticles; (c) linear aggregates; (d) hybrid systems; (e) mixed nanoparticle systems. After a general introduction to the magnetic heating phenomenology, we illustrate the different classes of nanoparticle systems and the strategic novelty they represent. We review some of the research works that have significantly contributed to clarify the relationship between the compositional and structural properties, as determined by the synthetic process, the magnetic properties and the heating mechanism.